1987
DOI: 10.1172/jci113080
|View full text |Cite
|
Sign up to set email alerts
|

Purification of human erythroid colony-forming units and demonstration of specific binding of erythropoietin.

Abstract: Morphological and biochemical studies of human colony-forming units-erythroid (CFU-E) have been hindered by their extreme rarity. Since burst-forming units-erythroid (BFU-E) develop into CFU-E, we used normal human blood BFU-E to generate large numbers of highly purified CFU-E in vitro. Using density centrifugation, sheep erythrocyte rosetting, surface immunglobulin positive cell depletion, adherence to plastic, and negative pn with monoclonal antibodies, human blood BFU-E were purified from 0.017 to 0368%, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
118
0
4

Year Published

1990
1990
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(126 citation statements)
references
References 34 publications
4
118
0
4
Order By: Relevance
“…The reason for this is most likely that whereas c-mpl appears to be expressed on primitive/multipotent progenitors [18][19][20], the EPO receptor might not be. In fact, previous studies have suggested that even the most primitive stages of erythroid progenitor cells might not yet express the EPO receptor [37,38].Based on these and other studies [5, 30,[33][34][35],39-431, we can conclude that TPO along with some other early-acting cytokines can promote viability of primitive HPC in the presence of little or no proliferation (Table 2). At least on Lin-Sca-1' bone marrow progenitor cells, TPO has a potent ability to promote viability of in vitro clonogenic and multipotent progenitor cells.…”
mentioning
confidence: 59%
See 2 more Smart Citations
“…The reason for this is most likely that whereas c-mpl appears to be expressed on primitive/multipotent progenitors [18][19][20], the EPO receptor might not be. In fact, previous studies have suggested that even the most primitive stages of erythroid progenitor cells might not yet express the EPO receptor [37,38].Based on these and other studies [5, 30,[33][34][35],39-431, we can conclude that TPO along with some other early-acting cytokines can promote viability of primitive HPC in the presence of little or no proliferation (Table 2). At least on Lin-Sca-1' bone marrow progenitor cells, TPO has a potent ability to promote viability of in vitro clonogenic and multipotent progenitor cells.…”
mentioning
confidence: 59%
“…However, unlike TPO, EPO had no effect on the viability of Lin-Sca-1' progenitors. The reason for this is most likely that whereas c-mpl appears to be expressed on primitive/multipotent progenitors [18][19][20] [37,38].…”
Section: Tpo Directly Promotes the In Vitro Viability Of Primitive Mumentioning
confidence: 99%
See 1 more Smart Citation
“…Epo supports the survival of late erythroid progenitors and enhances their proliferation and differentiation by binding to Epo receptor (Epor) (Krantz, 1991;Jelkmann, 2010;D'Andrea and Zon, 1990). Epo stimulates burst-forming unit-erythroid cells (BFU-e) expressing Epor on the surface, and successively colony-forming unit-erythroid cells (CFU-e), at sites of erythropoiesis (Broudy et al, 1991;Gregory and Eaves, 1978;Sawada et al, 1987). Further, mature erythrocytes are produced through proerythroblasts, erythroblasts, and reticulocytes.…”
Section: Introductionmentioning
confidence: 99%
“…A further negative selection and removal of contaminant cells with CD2, CD11b, CD16, and CD45 monoclonal antibodies was performed as previously described. 18,27 The day Ϫ1 BFU-Es were suspended in Iscove modified Dulbecco medium (IMDM) containing 20% heat-inactivated fetal calf serum (FCS), 5% heat-inactivated, pooled, human AB serum, 1% deionized bovine serum albumin (BSA), 5 ϫ 10 Ϫ5 M 2-mercaptoethanol, 10 g/mL insulin (Sigma, St Louis, MO), 2 U/mL erythropoietin (Amgen, Thousand Oaks, CA), 50 U/mL IL-3 (R&D Systems, Minneapolis, MN), 100 ng/mL SCF (Amgen), and streptomycin plus penicillin to generate ECFCs. After 5 days of culture the average purity of day Ϫ6 ECFCs was 60% or higher as measured by the plasma clot assay.…”
mentioning
confidence: 99%